Piracetam as a Therapeutic Agent for Doxorubicin-Induced Cognitive Deficits by Enhancing Cholinergic Functions and Reducing Neuronal Inflammation, Apoptosis, and Oxidative Stress in Rats - Vasudevan Mani; Syed Imam Rabbani; Ali Shariq; Palanisamy Amirthalingam; Minhajul Arfeen (MDPI AG, 2022)
Cancer chemotherapy is known to cause cognitive defects in patients. Our study investigated the effect of piracetam (PIRA; 200 or 400 mg/kg) against doxorubicin (DOX)-induced cognitive deficits in a rat model. The cognitive parameters were analyzed using elevated plus-maze, novel object recognition, and Y-maze tests. Acetylcholinesterase (AChE), neuroinflammatory mediators (cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2), nuclear factor-κB (NF-κB), tumor necrosis factor-alpha (TNF-α)), apoptotic proteins (B-cell lymphoma-2 (Bcl-2), Bcl2 associated X protein (Bax), cysteine aspartate specific protease-3 (caspase-3)), oxidative parameters (malondialdehyde (MDA), catalase (CAT), and glutathione (GSH)) were also determined in the brain. PIRA administration offered significant protection against DOX-induced cognitive deficits in all maze tests and restored cholinergic functions via a significant reduction in AChE levels. Additionally, PIRA suppressed DOX-induced neuroinflammatory mediators (COX-2, PGE2, NF-κB, and TNF-α), pro-apoptotic proteins (Bax and caspase-3), and oxidative stress (MDA). Besides, it facilitated antioxidant (CAT and GSH) levels. Hence, our study highlighted that the neuroprotective activity of PIRA against DOX-induced cognitive deficits can be linked to reductions of AChE levels, neuro-inflammatory mediators, pro-apoptotic proteins, and oxidative stress.